Cambios en la vida y subjetividad de las mujeres que se practicaron abortos :Historia de vida de dos mujeres quiteñas de clase media - Osejos Cadena, Vanessa Josefina (2015)
This thesis explains the changes in the lives of two middle-class women who had abortions. In Ecuador, abortion is legal on two circumstances: if at risk the lives of women and whether the product of a rape a woman with mental disabilities is. The observed problem is that due to the religious, moral and legal sanctions the practice of abortion is a clandestine experience. Such condition directly affects women´s health and her entire life and their relationships with family and society. This thesis answers the question: How the discourses and practices of the state, church and family influence the subjectivity of women who had abortions? In order to answer this question, is mainly used life stories and concepts that come mainly from the theory of practice and Feminism. In this thesis is argued that women who had abortions transformed their life and subjectivity and, this transformation have depended on their level of formal education, religious beliefs and their links with women's groups.